RIBEYE B-Domain Is Essential for RIBEYE A-Domain Stability and Assembly of Synaptic Ribbons - Shankhwar, Soni; Schwarz, Karin; Katiyar, Rashmi; Jung, Martin; Maxeiner, Stephan; Südhof, Thomas C.; Schmitz, Frank (Frontiers in Molecular Neuroscience, 2022)
Synaptic ribbons are presynaptic specializations that define eponymous ribbon synapses. Synaptic ribbons are largely composed of RIBEYE, a protein containing an N-terminal A-domain and a carboxyterminal B-domain that is identical with CtBP2, a NAD(H)-binding transcriptional co-repressor. Previously we showed that synaptic ribbons are completely absent in RIBEYE knockout mice in which the RIBEYE A-domain-encoding exon had been deleted, but CtBP2 is still made, demonstrating that the A-domain is required for synaptic ribbon assembly. In the present study, we asked whether the RIBEYE B-domain also has an essential role in the assembly of synaptic ribbons. For this purpose, we made use of RIBEYE knockin mice in which the RIBEYE B-domain was replaced by a fluorescent protein domain, whereas the RIBEYE A-domain was retained unchanged. We found that replacing the RIBEYE B-domain with a fluorescent protein module destabilizes the resulting hybrid protein and causes a complete loss of synaptic ribbons. Our results thus demonstrate an essential role of the RIBEYE B-domain in enabling RIBEYE assembly into synaptic ribbons, reinforcing the notion that RIBEYE is the central organizer of synaptic ribbons.